2019
DOI: 10.3390/f10020113
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil C:N:P Stoichiometry and Microbial Structure along Soil Depth in Two Forest Soils

Abstract: The effects of interactions of soil type and soil depth on soil C:N:P stoichiometry and microorganisms are poorly understood. In this study, soil samples (0–10, 10–20, 20–30, 30–50, 50–100 cm) were collected from two soil types (Haplic luvisols and Eutric cambisols) in Sabina przewalskii Kom. forest of Qinghai-Tibet Plateau. The soil C:N ratio and soil microbial biomass (SMB) measured using phospholipid fatty acid in Eutric cambisols were significantly higher than in Haplic luvisols, while soil C:P and N:P rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The lower availability of phosphorus in the subsoil than in the topsoil could be attributed to the low solubility of phosphorus in slightly alkaline soils (El‐Baruni & Olsen, ), again affecting the vertical patterns through our 20‐m‐deep soil profile. The decrease in microbial biomass carbon with soil depth was also consistent with previous studies (Eilers et al, ; Hu et al, ; Zhang et al, ), that is, microbial biomass carbon decreased drastically from the surface soil to a depth of 1 m of the subsoil, and then the change kept relatively steady in deep soils thereafter (Eilers et al, ). The excessive depletion of water in deep soils in R .…”
Section: Discussionsupporting
confidence: 90%
“…The lower availability of phosphorus in the subsoil than in the topsoil could be attributed to the low solubility of phosphorus in slightly alkaline soils (El‐Baruni & Olsen, ), again affecting the vertical patterns through our 20‐m‐deep soil profile. The decrease in microbial biomass carbon with soil depth was also consistent with previous studies (Eilers et al, ; Hu et al, ; Zhang et al, ), that is, microbial biomass carbon decreased drastically from the surface soil to a depth of 1 m of the subsoil, and then the change kept relatively steady in deep soils thereafter (Eilers et al, ). The excessive depletion of water in deep soils in R .…”
Section: Discussionsupporting
confidence: 90%
“…Organic C content typically declines with soil depth because of reduced nutrient input from plant litter and root exudates (Fierer et al, 2003). The decrease in microbial biomass, measured in our study as DNA content, with increasing soil depth was also consistent with results from previous studies (Eilers et al, 2012;Hu et al, 2019;Zhang et al, 2019). At our forest sites, DNA content decreased FIGURE 6 | Differentially abundant fungal genera of topsoil (soil layers L1 and L2) vs. subsoil (soil layers L5 and L6).…”
Section: Soil Physicochemical Variables Affect Microbial Community Structuressupporting
confidence: 90%
“…Soil C, N, and P contents and stoichiometry vary with depths (Hu et al 2019), therefore, under-standing how variations in physicochemical characteristics along the soil pro le shape microorganism communities is essential to understanding the below-ground ecological processes. Previous studies revealed that soil microbial communities are determined by several abiotic factors (Andersen et al 2013 (Lamit et al 2017) were factors that affecting microbial communities.…”
Section: Introductionmentioning
confidence: 99%